(3GdGSJZfGA aj CMcGe GdGSJKfGAs - (3CHhGdYHGS TgGH GdOjf CMeO Hf GOQjS Hf YHO GdQMef GdUfgGLj GdbQGaj GdeGdcj,J (B684 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdefaQO HGdCRdjI hGdHbGA hGdeJhMO HGdEeGJI hGdEMjGA CeG HYO (B: (3aEf GdESJKfGA GdYQHjI ChbY Gddg JYGdi di ajgG eHGMK LejdI , hbhGYO LdjdI ChOYJ ajgG TQM GdeMUhd LedkG cKjQI s
(3BNQgG (B:s
(3bdJ JNQL Ydi CMO GdCbhGd GdCQHYI GdJi JbOe HjGfgG ai HGH eG jLhR ESJJKfGDg Je gPG GdcJGH HYhf Gddg Gdedc GdhgGH , hGddg Gdehab ddUhGH Hefg hcQeg hNai dWaI s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B94 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B158s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B72s
Keywords: (3GdbQGAGJ hGdJLhjOs